RE-MAPPING PENDIDIKAN ‘ULŪM AL-QUR’ĀN DI PERGURUAN TINGGI AGAMA ISLAM (PTAI) - Hamdiah Hamdiah (Universitas Islam Negeri Ar-Raniry, 2015)
This article attempts to explain and describe real condition of ‘ulūm al-Qur’ān teaching within Islamic Higher Education Institute in Indonesia. Some findings of the research show that the discipline sould be re-mapped and revitalized in order to maintain and keep the Islamic scientific tradition which has deep Islamic rooted but it the same time open to adopt new methods of Quranic exegesis from other as long as has been Islamized so that compliant and in line with the Islamic values and Islamic religious tradition.